2016
DOI: 10.1111/jfbc.12311
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Endogenous Protease and the Changes in Proteolytic Activity ofAcetes vulgarisandMacrobrachium lanchesteriDuringKapiProduction

Abstract: Characteristics of endogenous proteases of shrimp, Acetes vulgaris (AP) and Macrobrachium lanchesteri (MP) as well as the changes in proteolytic activity during Kapi production were investigated. Maximal activity of AP and MP was found at pH 7, 60C and pH 8, 60C, respectively. Activity of both proteases decreased with increasing NaCl concentration (0–30%). Both extracts were strongly inhibited by N‐ethylmaleimide‐phenylmethane‐sulfonyl fluoride (PMSF) and soybean trypsin inhibitor (SBTI), suggesting that major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…These changes in free amino acid during processing might be influenced by endogenous proteases in raw material and microbial proteases proliferated during processes. Our previous study revealed that proteolytic activity of fresh shrimp was decreased after being salted and dried, but continuously increased during fermentation up to 30 days (Pongsetkul et al 2016). Those proteases more likely played a profound role in protein degradation, thus contributing to the liberation of free amino acids throughout Kapi production.…”
Section: Changes In Free Amino Acid Compositionmentioning
confidence: 96%
“…These changes in free amino acid during processing might be influenced by endogenous proteases in raw material and microbial proteases proliferated during processes. Our previous study revealed that proteolytic activity of fresh shrimp was decreased after being salted and dried, but continuously increased during fermentation up to 30 days (Pongsetkul et al 2016). Those proteases more likely played a profound role in protein degradation, thus contributing to the liberation of free amino acids throughout Kapi production.…”
Section: Changes In Free Amino Acid Compositionmentioning
confidence: 96%
“…Highly unsaturated fatty acids are more likely to oxidise, which lowers their nutritional value and produces a disagreeable taste and odor (Chotphruethipong and Benjakul, 2019). Proteolytic enzymes and gut bacteria break down a significant amount of proteins, resulting in the production of ammonia and nitrogenous substances, which compromises the safety and sensory qualities of the proteins (Olatunde et al, 2019;Pongsetkul et al, 2017).…”
Section: Fish Sample Chemicals and Othermentioning
confidence: 99%
“…Highly unsaturated fats are more susceptible to oxidation, thus reducing their nutritive value and generating unpleasant odor and taste (Chotphruethipong & Benjakul, 2019; Maqsood et al., 2014). Large proportions of proteins are degraded by proteolytic enzymes and gut microflora to produce ammonia and nitrogenous compounds, affecting their safety and sensory attributes (Hsieh & Kinsella, 1989; Olatunde et al., 2019b; Pongsetkul et al., 2017).…”
Section: Introductionmentioning
confidence: 99%